In situ templating synthesis of mesoporous Ni–Fe electrocatalyst for oxygen evolution reaction. Issue 39 (18th June 2020) - Wang, Ya; Yu, Jun; Wang, Yanding; Chen, Zhuwen; Dong, Lei; Cai, Rongming; Hong, Mei; Long, Xia; Yang, Shihe
Abstract : A stable mesoporous Ni–Fe–O electrocatalyst with high OER efficiency is constructed using mesoporous fumed silica as a template. Abstract : Low-cost and efficient electrocatalysts with high dispersion of active sites and high conductivity are of high importance for oxygen evolution reaction (OER). Herein, we use amorphous mesoporous fumed silica (MFS) as a skeleton material to disperse Ni 2+ and Fe 3+ through a simple impregnation strategy. The MFS is in situ etched away during the OER process in 1 M KOH to prepare a stable mesoporous Ni–Fe electrocatalyst. The high specific surface area and abundant surface silanol groups in the mesoporous fumed silica afford rich anchor sites for fixing metal atoms via strong chemical metal–oxygen interactions. Raman and XPS investigations reveal that Ni 2+ formed covalent bonds with surface Si–OH groups, and Fe 3+ inserted into the framework of fumed silica forming Fe–O–Si bonds. The mesoporous Ni–Fe catalysts offer high charge transfer abilities in the OER process. When loaded on nickel foam, the optimal 2Ni1Fe-MFS catalyst exhibits an overpotential of 270 mV at 10 mA cm −2 and a Tafel slope of 41 mV dec −1 . Notably, 2Ni1Fe-MFS shows a turnover frequency value of 0.155 s −1 at an overpotential of 300 mV, which is 80 and 190 times higher than that of the state-of-the-art IrO2 and RuO2 catalysts. Furthermore, 2Ni1Fe-MFS exhibits 100% faradaic efficiency, large electrochemically active surface area, and good long-term durability, confirming its outstanding OER performance. Such high OER efficiency can be ascribed to the synergistic effect of high surface area, dense metal active sites and interfacial conductive path. This work provides a promising strategy to develop simple, cost-effective, and highly efficient porous Ni–Fe based catalysts for OER.